The moderating role of autonomy in the relationship between advisory services, risk management, and integrity system: Indonesia evidence - Sihombing, Ranto Partomuan; Murniati, Monica Palupi (Jurnal Akuntansi dan Auditing Indonesia, 2024)
Since 2014, Indonesia has implemented the Integrity System (IS) policy across ministry and government institution work units to address the ongoing challenge of corruption. Inspectorate auditors play a pivotal role in ensuring the successful implementation of the IS, providing both advisory services and risk management support within these units. This study aims to investigate the moderating role of autonomy in the relationship between advisory services, risk management, and the integrity system. A survey of 103 inspectorate auditors from various ministries and government institutions in Indonesia was conducted to explore these dynamics. Drawing on role theory, our findings reveal two key insights: (1) advisory services and risk management significantly enhance the implementation of the IS, and (2) autonomy strengthens the positive relationship between risk management and the IS. This research addresses the underexplored debate on the primary roles of internal auditors, offering novel insights within the Indonesian context.